2015
DOI: 10.12735/jfe.v3i1p31
|View full text |Cite
|
Sign up to set email alerts
|

How Credit Affects the Poor Household’s Expenditure?: A Case Study of Vietnam

Abstract: This paper aims to clarify the impact of the credit for the expenditure of poor households in Vietnam. We have used Difference in Difference (DID) methods to estimate the panel data from Vietnam Living Standard Survey (VLSS) for the period of 2010-2012. The results showed that the credit has a positive influence to the average expenditure of the poor households, whether in formal credit or informal credit. However, informal credit is still a very important source of credit for poor households in Vietnam becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…The ATT for NNM was Gh¢ 3,503.333 (US$ 606.11) while KM and SM were Gh¢ 4296.939 (US$ 743.42) and Gh¢ 5502.660 (US$ 952.02), respectively. The finding follows Giang et al (2015) who reported that credit increase expenditure. It must be noted that, since trade credit is seen as an alternative credit source, credit could be the same as trade credit in the extreme case.…”
Section: Resultssupporting
confidence: 71%
“…The ATT for NNM was Gh¢ 3,503.333 (US$ 606.11) while KM and SM were Gh¢ 4296.939 (US$ 743.42) and Gh¢ 5502.660 (US$ 952.02), respectively. The finding follows Giang et al (2015) who reported that credit increase expenditure. It must be noted that, since trade credit is seen as an alternative credit source, credit could be the same as trade credit in the extreme case.…”
Section: Resultssupporting
confidence: 71%